Effect of teaching program by using (M.U.R.D.E.R) strategy in teaching of technical achievement for shot put event for students - Mohsin Saadoon, Hussein; Khalid Abdul Wahid, Zahraa; Mousa Al-Saedi, Ali Khalaf (Journal of Neonatal Surgery, 2025)
This study aims to prepare units of teaching by using (M URDER) strategy to teach technical achievement for shot put event for the students. The researcher used experimental approach by two equalized groups. The society of the research were (36) students in the first grade in College of physical education and sport sciences .Meesan university for the season (2022/2023). The sample of the study were (28) students divided randomly into two groups control and experimental. Every group contains of (14) students. The percentage of the sample was (78) of the original society. Teaching program spent 4 weeks. Two units in every week. The time of the two units is (180) minutes. Finally the researcher treated with results statistically by using of the statistical bag (spss). The researcher reached to realize many conclusions. The first is that the using of (M URDER ) strategy realized the targets and the purposes to teach the technical achievement for shot put event for students and the other purpose of the research represented by capability of the students to create the suitable solutions in the teaching because of its dependence on mental, visual and the listening operations individually or collectively. The researcher recommended to use (M URDER ) strategy in the lessons of the subject of track and field event in addition to organize teaching approach which should be agreed with steps of (M URDER ) strategy which could lead the specialists and the experts in the physical education field to realize the targets of the teaching.